1998
DOI: 10.1029/98ja02419
|View full text |Cite
|
Sign up to set email alerts
|

Generation of electrostatic whistler wave by extraordinary EM wave

Abstract: Abstract. The parametric decay instability of an extraordinary electromagnetic wave into an electron plasma wave and an electrostatic whistler wave has been studied. Explicit expressions for the homogeneous growth rate and threshold electric field have been presented for this instability. The relevance of the present parametric process has been pointed out to explain the generation of whistler mode radiations in the SL-2 experiment as well as in auroral magnetosphere (auroral hiss).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Cattell et al [2008] have demonstrated that the whistler waves bear quasi-electrostatic character near resonance cone. Sharma et al [1998] studied the generation of electrostatic whistler waves by extraordinary electromagnetic waves near resonance cone angle. As far as resonance cone angle is concerned, it is being very important for electrostatic whistler wave propagation especially in radiation belts.…”
Section: Introductionmentioning
confidence: 99%
“…Cattell et al [2008] have demonstrated that the whistler waves bear quasi-electrostatic character near resonance cone. Sharma et al [1998] studied the generation of electrostatic whistler waves by extraordinary electromagnetic waves near resonance cone angle. As far as resonance cone angle is concerned, it is being very important for electrostatic whistler wave propagation especially in radiation belts.…”
Section: Introductionmentioning
confidence: 99%
“…Mace, 1998;Gary and Cairns, 1999;Zhang et al, 1999b), to the anisotropy of the parallel velocity distribution which appears through heat transfer (Forslund et al, 1972;Gary et al, 1975;Jie Zhao et al, 1996), or to the presence of suprathermal electron fluxes or beams (Kennel and Wong, 1967;Tokar et al, 1984;Ergun et al, 1993;Omelchenko et al, 1994). Whistlers can also be excited by nonlinear wavewave processes; let us cite, for example, the decay of a Langmuir wave into another Langmuir wave with the participation of whistlers and lower hybrid waves, as considered by Kuo and Lee (1989), Leyser (1991), Sawhney et al (1996) and Sharma et al (1998) for ionospheric and laboratory experiment conditions, and only by Abalde et al (1998), Chian and Abalde (1999) and Luo et al (2000) for solar wind plasma conditions.…”
Section: Introductionmentioning
confidence: 99%